Pelatihan Teknik Motif Tie-Dye Untuk Meningkatkan Keterampilan Kreativitas dan Ketrampilan Desain pada Kaos di FKDB (Forum Komunitas Difabel Boyolali) - Shofia, Firza; Bhirawa Khoiru Almahdi; Sigit Hartono; Ama Zakiya; Febiana Nurul Hidayah; Syarifa Nissa Fauziah; Afifah Cahya Widya Pratama; Faradina Putri Rachmadania Kuspriyanto; Flanela Ramadhani Rahma Saputri; Shafati Hajran Mahmudati; Ilham Priadythama (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The Boyolali Disability Community Forum (FKDB) faces the challenge of developing creative programs that can enhance the skills and creativity of members with various disabilities. The tie-dye training program, conducted as part of this community service activity, aims to empower FKDB members through the development of skills and creativity that have economic value. The implementation method uses a potential development method with a participatory approach, involving FKDB members and mentors. During the program, the skills and motivation of participants were successfully improved despite physical limitations and limited equipment. The active support of mentors and the enthusiasm of members were key to its success. Conclusions indicate that the tie-dye training has a positive impact on the skills, creativity, and well-being of FKDB members.